(untitled) (Italian Journal of Public Health, 2011)
Following the report of many cases of Legionnaires’ disease associated with accommodation facilities such as hotels, spas, workplaces, hospitals and nursing homes, we verified if Legionella pneumophila and Legionella spp. were present in some of those structures in Tuscany, in order to estimate the species and serogroups in circulation. Legionella pneumophila serogroup 1 (30.9%) was the most frequently isolated species along with serogroups 3 (16.1%) and 6 (13.3%); these three serogroups are identified, in literature, as those most responsible for Legionnaires’ disease (LD). Studying all analyzed structures, we found some parts of the water system where Legionella concentration was higher than 103 CFU/L, indicated, in Italy, as the maximum admitted concentration value above which a decontamination treatment is necessary when one or more cases of healthcare-acquired Legionnaires’ disease are observed. Moreover disinfection is recommended in any case when counts exceed 10 4 CFU/L. Consequently, in order to prevent cases of Legionnaires’ disease, a continuous surveillance of the water systems of all accommodation facilities is necessary, with particular attention to hospitals and nursing homes where immunocompromised patients lodge, so as to promptly estimate the presence of the pathogen and consequently plan the most suitable intervention activities. We concluded that, in any structure, a continuous surveillance and disinfecting treatment of water systems is necessary. Moreover, after any disinfection treatment the temperature of the hot water flowing in the system must be necessarily maintained near 51°C in order to minimize the probability of recontamination from Legionella and limit the risk of LD in consumers.